CAMK1D triggers immune resistance of human tumor cells refractory to Anti-PD-L1 treatment - Volpin, Valentina; Michels, Tillmann; Sorrentino, Antonio; Menevse, Ayse N.; Knoll, Gertrud; Ditz, Madlen; Milenkovic, Vladimir M.; Chen, Chih-Yeh; Rathinasamy, Anchana; Griewank, Klaus; Boutros, Michael; Haferkamp, Sebastian; et al. (Cancer immunology research, 2020)
The success of cancer immunotherapy is limited by resistance to immune checkpoint blockade. We therefore conducted a genetic screen to identify genes that mediated resistance against CTLs in anti-PD-L1 treatment-refractory human tumors. Using PD-L1-positive multiple myeloma cells cocultured with tumor-reactive bone marrow-infiltrating CTL as a model, we identified calcium/calmodulin-dependent protein kinase 1D (CAMK1D) as a key modulator of tumor-intrinsic immune resistance. CAMK1D was coexpressed with PD-L1 in anti-PD-L1/PD-1 treatment-refractory cancer types and correlated with poor prognosis in these tumors. CAMK1D was activated by CTL through Fas-receptor stimulation, which led to CAMK1D binding to and phosphorylating caspase-3, -6, and -7, inhibiting their activation and function. Consistently, CAMK1D mediated immune resistance of murine colorectal cancer cells in vivo. The pharmacologic inhibition of CAMK1D, on the other hand, restored the sensitivity toward Fas-ligand treatment in multiple myeloma and uveal melanoma cells in vitro. Thus, rapid inhibition of the terminal apoptotic cascade by CAMK1D expressed in anti-PD-L1-refractory tumors via T-cell recognition may have contributed to tumor immune resistance.
Gesehen am 02.02.2021